Effect of Black Garlic and Curcuma Addition on Carcass and Abdominal Fat of Broilers - Ariyani Tanti; Nurhayati; Berliana; Nelwida (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2022)
The purpose of this study was to evaluate the addition of black garlic & Curcuma zanthorrhiza Roxb on broiler carcass and abdominal fat. A completely randomized design (CRD) was conducted with five treatments and four replications. Each replication consisted of 10 chickens and a total of 200 broilers was used. The broilers were randomly allocated into 20 unit of cages. The feeding treatments were P0 = 100% commercial feed without black garlic powder (BGP) and curcuma powder (CP) addition as a feeding control, P1 = P0 + 3% BGP + 0% TP, P2 = P0 + 2% BGP + 1% TP, P3 = P0 + 1% BGP + 2% TP, and P4 = P0 + 0% BGP + 3% TP. The measured variables were feed consumption, slaughtered weight, carcass weight, and abdominal fat percentage. Analysis of variance (ANOVA) was used to analyze the data and the significant result was tested with Duncan's multiple range test to determine whether the treatment had a significant effect. According to the results of this study, the utilization of black garlic and curcuma in broiler diets was not significantly different in all variables. It was concluded that the usage of black garlic and curcuma did not increase carcass weight and abdominal fat in broilers. Key words: abdominal fat, black garlic, broiler, carcass, Curcuma zanthorrhiza Roxb